Collaborative work in international university networks (Ágora de Heterodoxias, 2016)
Our scientific journal, which operates as a network between international peers, has been strengthened in diversity and interdependence, with the purpose of stimulating the systematization of intellectual production generated in the academic community. And in this third issue we publish the results of research, that are the product of the attendance of scientists from different disciplines dialogue beyond the physical walls of their institutions secondment to cooperate in academic networks based on a common goal. Make collaborative and knowledge sharing is promoted intensively, to promote exchange between: university researchers, disciplines and socio–productive environment.